2007
DOI: 10.1266/ggs.82.123
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of barley chromosome 5H in common wheat

Abstract: We dissected barley chromosome 5H added to common wheat by a genetic method or the gametocidal system. Firstly, we induced chromosomal breaks in the offspring of a 5H addition line of common wheat carrying a gametocidal chromosome and cytologically screened for plants with structural chromosomal changes involving 5H, such as deletions and translocations. Secondly, we screened the progeny of such plants to establish common wheat lines carrying structurally changed chromosomes containing single segments of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…These 7H deletion and translocation lines were then used for the physical mapping of the 7H barley chromosome (Serizawa et al 2001). Nasuda et al (2005), Ashida et al (2007) and Sakai et al (2009) performed deletion mapping on barley chromosomes 7H, 5H and 3H using barley dissection lines and barley-specific EST Euphytica (2014) 195:315-329 321 markers. The barley dissection lines were produced from CS-Betzes addition lines, so they all carried chromosome segments from Betzes barley.…”
Section: Chromosome Pairing In Wheat 3 Barley Hybridsmentioning
confidence: 99%
“…These 7H deletion and translocation lines were then used for the physical mapping of the 7H barley chromosome (Serizawa et al 2001). Nasuda et al (2005), Ashida et al (2007) and Sakai et al (2009) performed deletion mapping on barley chromosomes 7H, 5H and 3H using barley dissection lines and barley-specific EST Euphytica (2014) 195:315-329 321 markers. The barley dissection lines were produced from CS-Betzes addition lines, so they all carried chromosome segments from Betzes barley.…”
Section: Chromosome Pairing In Wheat 3 Barley Hybridsmentioning
confidence: 99%
“…For example, Nasuda et al (2005) and Ashida et al (2007) mapped barley EST markers on the barley chromosome deletion stocks and estimated the physical location of these ESTs. Although the resolution in segmental allocation of markers was low in wheat deletion stock mapping (Sorrells et al, 2003), the approach is a useful first step in developing BAC contigs for genome sequencing.…”
Section: Snp Typing 17% Caps 9%mentioning
confidence: 99%
“…Endo (1999, 2000) demonstrated that chromosome 2C is capable of inducing structural changes in every barley chromosome in 'Chinese Spring'. Shi and Endo (2000), Ashida et al (2007) and Sakai et al (2008) employed the Gc system with chromosome 2C or 3C SAT to induce structural changes in barley chromosomes 3H, 5H and 7H, and establish so-called 'barley dissection lines' of common wheat. These works showed that chromosome 3C SAT is as effective as chromosome 2C in inducing structural rearrangements in barley chromosomes.…”
Section: The Gametocidal Systemmentioning
confidence: 99%
“…Serizawa et al (2001) conducted deletion mapping of AFLP and STS markers that had been used in a genetic mapping and translocation mapping (Künzel et al 2000) and found that the marker orders matched previous maps. Using the barley dissection lines and barley-specific EST markers (Nasuda et al 2005a), Nasuda et al (2005a), Ashida et al (2007) and Sakai et al (2009) conducted deletion mapping of barley chromosomes 7H, 5H and 3H, respectively. All these studies revealed that the distal regions of the barley chromosomes are richer in EST markers than the proximal regions.…”
Section: Cytological Mapping Of Barley Chromosomesmentioning
confidence: 99%